Ecological Studies on Borreria Articularis (Linn. F.) F.N. Will II. Water Relations - Babu, V Ramesh; Joshie, M C (Annals of Arid Zone, 2016)
Borreria articularis show reduction of leaf surface during the winter compared to plants growing in warm monsoon. However, this does not appear to be due to water condition. Stomata open and close in response to light and no stomata1 regulation of transpiration up to 29 per cent water deficit has been observed. Transpiration flow from plants was found to reach the peak by 11.00 hours and continue upto (5.00 hours. However, rates of evaporation and transpiration were found far higher in the growing season as compared with those recorded in winter. Maximum replenishment of lost water ( by gain in water deficits ) in plants occurred at 18.00 hours till midnight in a diurnal cycle.